Evaluasi pakan suplemen terproteksi berdasarkan kecernaan bahan kering, kecernaan bahan organik dan pH secara In Vitro - Ahmad Pramono; Yulia Arnia Sari; Sahrul Romadhon; Muhammad Cahyadi; Dimas Fajar Nugroho (Livestock and Animal Research, 2022)
Objective: The research was conducted to evaluate protected feed supplement made of soybean groats and worm flour (Lumbricus rubellus) based on in vitro dry matter and organic matter digestibility and pH rumen fluids as a single feed or concentrate.Methods: The method used in vitro two-stage with observation of stage I (Rumen) and stage II (Total). Completely Randomized Design (CRD) with 6 treatments and 5 replications was used. The treatments were P1 = soybeans groats, P2 = protected soybeans groats, P3 = worm flour, P4 = protected worm flour, P5 = concentrate (50% rice bran + 50% pollard) and P6 = 75% concentrate + 20% protected soybeans groats + 5% protected worm flour. The 37% formaldehyde was used to protect the soybean groats. The addition was determined at 1% from total dry matter. The data obtained were analyzed by Analysis of Variance with Orthogonal Counter Test.Results: The result obtained for P2 was markedly lower than that of P1 on rumen KcBK and KcBO, while no significant effect was seen concerning the total KcBK and KcBO. Accordingly, similar trend was observed for P4 that was significantly lower in comparison to that of P3. Further, P1 and P2 when compared to P3 and P4 possessed the lowest score among variables. Meanwhile, no effect on variables was seen when P5 compared to P6. Additionally, With regard to P6, the result on KcBK and KcBO were significantly higher compared to remaining treatments.Conclusions: The results could be concluded that the 37% formaldehyde was used to protect the soybean groats. The addition was determined at 1% from total dry matter can reduce dry matter digestibility and organic matter digestibility of soybean groats and worm flour (Lumbricus rubellus) in the rumen and it can be degraded and digested in the abomasum to the small intestine. Therefore, pH of rumen fluid is optimal, so it does not interfere with the fermentation in the rumen.